Determination of criteria for the assessment of embryo quality with good implantation predictability on a model of unstimulated in vitro fertilization cycles – Prediction of implantation in unstimulated cycles - Mojca Čižek Sajko; Veljko Vlaisavljević (Zdravniški Vestnik, 2011)
Background: In unstimulated in vitro fertilization cycles we analysed which criteria for the assessment of day-3-embryo quality were the most important predictive factors of successful implantation. Methods: A retrospective analysis of 115 unstimulated in vitro fertilization (IVF) cycles, terminated by embryo transfer (ET) on day 3 post follicular aspiration, was done. The embryos were evaluated according to three criteria: (i) blastomere fragmentation, (ii) blastomere number on the day of ET and (iii) blastomere cleavage dynamics. The impact of individual criteria, and of combinations of several criteria for embryo quality assessment, on implantation was established. Results: The impact of embryo quality on implantation could only be confirmed in the case when the embryo was evaluated on the basis of blastomere fragmentation and blastomere cleavage dynamics simultaneously (χ2 = 5.23; P< 0.05). In such cases the implantation rate amounted to 27.0 % (20/74) in good quality embryos and 9.8 % (4/41) in poor quality embryos. The predictive value of implantation for the so defined embryo quality was 3.43 (95 % CI = 1.08–10.84). Conclusion: Embryo quality, defined by blastomere fragmentation and blastomere cleavage dynamics simultaneously, proved to be a good predictive factor of implantation. In good quality embryos, the odds for implantation were 3.43 times higher than in embryos of poor quality.